Biodegradation of low concentration of monochloroacetic acid-degrading Bacillus sp. TW1 isolated from terengganu water treatment and distribution plant - Ahmad Hafiz, Zulkifly; Roslan, D.D; Hamid, A.A.A; Hamdan, S.b (2010)
Haloacetic acids (HAAS) are group of chemicals formed due to disinfection by products that can be detected during chlorination and chlorammatton of processed drinking water In this study. Bacillus sp strain TW1 identified by morphological/biochemical and PCR-amplified 16$ rRIIA gene was isolated from Kuala Torongganu water treatment and distribution plant TW1 was isolated due to its ability to grow in low concentration of monochloroacetic acid (MCA) of 0 5 mtd. 10 times tower than normal MCA as sole carbon and energy source Bacterial cell culture was grown in liquid minimal medium, pH 6 5 at 30t on rotary shaker (150 rpm) Degradation of monochloroacetic acid was detected by measuring the amount of chloride ion released in the liquid minimal medium Strain 1W1 degraded monochloroacetic acid at best mth maximum chloride ion released of 0 32 lumol CI mL' using 0 5